2015
DOI: 10.5424/sjar/2015133-6717
|View full text |Cite
|
Sign up to set email alerts
|

Ensiled citrus pulp as a by-product feedstuff for finishing pigs: nutritional value and effects on intestinal microflora and carcass quality

Abstract: Forty pigs of 76.8 ± 4.2 kg body weight were fed four different diets varying in ensiled citrus pulp (ECP) inclusion level (0, 50, 100, and 150 g of ECP/kg of diet on dry matter base). The trial lasted 5 weeks. During the last week, faecal samples were obtained to calculate apparent nutrient digestibility; also volatile fatty acids (VFA) content in faeces was determined. The digestible energy and protein of ECP was estimated by regression analysis. During the trial faecal samples were collected to determine en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
3
14
0
1
Order By: Relevance
“…In particular, citrus peel, which is most often discarded as waste, contains the highest amount of polymethoxylated flavones compared to other edible parts of the fruit [144]. A study evaluated the effects of including three different levels of ensiled citrus pulp (50, 100 and 150 g/kg diet) in finishing pig diets on carcass quality and other parameters [145]. The results showed an increase of fat deposition at gluteus medius in pigs fed with 50 and 100 g of additive/kg, while the inclusion of 150 g/kg has resulted in a reduction in both energy digestibility and fat deposition.…”
Section: Monogastricmentioning
confidence: 99%
“…In particular, citrus peel, which is most often discarded as waste, contains the highest amount of polymethoxylated flavones compared to other edible parts of the fruit [144]. A study evaluated the effects of including three different levels of ensiled citrus pulp (50, 100 and 150 g/kg diet) in finishing pig diets on carcass quality and other parameters [145]. The results showed an increase of fat deposition at gluteus medius in pigs fed with 50 and 100 g of additive/kg, while the inclusion of 150 g/kg has resulted in a reduction in both energy digestibility and fat deposition.…”
Section: Monogastricmentioning
confidence: 99%
“…However, the nutritional value of dried citrus pulp for pigs reported in different databases [ 11 , 12 , 13 , 14 ] suggests an appreciable digestible energy content from 12.8 to 14.0 MJ/kg dry matter (DM), although the information available from in vivo assays is scarce [ 15 , 16 , 17 ] and shows discrepancies (11.7, 13.3 and 15.6 MJ DE/kg dry matter, respectively). Additionally, a previous study with wet ensiled citrus pulp in growing pigs reported a very low energy value (7.0 MJ DE/kg DM [ 9 ]), compared with other sources of citrus pulp.…”
Section: Introductionmentioning
confidence: 99%
“…These results do not agree with the findings of Cerisuelo et al (2010) , who demonstrate a decrease of feed intake with citrus-based product supplementation at 50 and 100 g/kg on pigs. Other authors also show a decline of feed intake from pigs supplemented with citrus-based product at 10, 20, and 40 g/kg ( Baird et al, 1974 ) and at a dosage between 50 and 150 g/kg ( Moset et al, 2015 ). We used 2,500 ppm but in addition to the dose difference, these discrepancies may be explained by the origin of the tested citrus.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, citrus product available on the market can be composed of a unique sort of citrus or a combination of them. In accordance to this, the active compounds vary substantially, which may lead to a large variability of efficiency of the product ( Moset et al, 2015 ). Standardization of these extracts is primordial in order to guarantee their effect independently from the period at which the citrus is collected.…”
Section: Discussionmentioning
confidence: 99%